Comparison of Practical Investigations for CO Emissions Emitted From Single Cylinder S. I. Engine Fueled With Different Kinds of Hydrocarbon Fuels and Hydrogen - Khalil Ibrahim Abaas (Al-Khwarizmi College of Engineering – University of Baghdad, 2019)
Liquefied petroleum gas (LPG), Natural gas (NG) and hydrogen were all used to operate spark ignition internal combustion engine Ricardo E6. A comparison of CO emissions emitted from each case, with emissions emitted from engine fueled with gasoline as a fuel is conducted.